Etika Makan dan Minum Yang Menyehatkan Dalam Prespektif Al-Qur’an - Ferry Martedi ZA; Gia Rosdiana Tirta; Dwi Noviani; Nyimas Anisah Muhammad (STIKes Ibnu Sina Ajibarang, 2023)
Eating and drinking are primary needs for humans, where if humans do not eat, the energy needed by the body will not be met, the lack of the body's need for energy will result in the body becoming weak and diseases that will easily attack. So then don't, because the body needs food and drink, humans take action by eating and drinking anything without knowing whether the substances contained are halal or not. Because in Islamic law it has been regulated in the Al-Qur'an and Hadith that certain foods and drinks can and cannot be consumed. With these rules, humans can choose so that we can avoid harm and become benefits for our bodies.